KAJIAN PEMBELAJARAN ALAT MUSIK DRUM BAND DI SDN CITENGAH KABUPATEN SUMEDANG - Nur Aulia, Siti Alawiah; Gusrayani, Diah; Julia, Julia (Jurnal Pena Ilmiah, 2017)
Music is an idea of feelings that are written in tone and rhythm. The learning of musical instruments applied in elementary school is very supportive during its growth and development, because giving practical experience means opening the mind to be ready to receive broad insights and knowledge. This study aims to examine the learning of Drum Band music instrument at SDN Citengah which has contributed to the improvement of musical skill of the students. Qualitative descriptive is the right method to describe the phenomenon. Description of the learning process, learning outcomes, and factors supporting the success of learning into the formulation of the problem in this study. Data collection techniques used to describe the learning of musical instruments Drum Band is an interview technique, observation, documentation, and field notes. The results describe the learning process that has three stages, namely the repetition stage, the stage of giving the material, and the training stage. Lessons learned have improved students' musical skills and improved their discipline.